The Effect of Character-Based Learning in Education for Sustainable Development on Arabic Language Learning in Higher Education - Devy Aisyah; Melisa Rezi; Adam Mudinillah; Abdul Aziz (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2024)
Because a person's character can be shaped at will according to his environment, friends, education, and so on. But the character of the attack cannot be seen from behavior alone but can also be seen from his words and the language he speaks. Currently there are many people who are highly educated but do not pay attention to their speech to those around them. The purpose of this study is to discuss how important character building is for a student who learns Arabic and has good speech, and the development of good speech. This method uses quantitative methods, data is processed using ANOVA. The results of this study show that character education from childhood is a good basis for the growth of a child. It also has a positive impact on learners who learn Arabic by not learning half and half and choose a good language. Character learning from an early age can form the character of a good child, paying attention to our speech in educating a child's character will also have a positive impact on their speech which becomes good when a child who is already in advanced level and he speaks with harsh words either using mother tongue or Arabic